1996
DOI: 10.1177/036354659602400321
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Iliotibial Band Friction Syndrome in Runners

Abstract: We propose a biomechanical model to explain the pathogenesis of iliotibial band friction syndrome in distance runners. The model is based on a kinematic study of nine runners with iliotibial band friction syndrome, a cadaveric study of 11 normal knees, and a literature review. Friction (or impingement) occurs near footstrike, predominantly in the foot contact phase, between the posterior edge of the iliotibial band and the underlying lateral femoral epicondyle. The study subjects had an average knee flexion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
2
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 23 publications
2
110
2
8
Order By: Relevance
“…This finding provides further evidence that knee flexion, by itself, does not play a significant role in the aetiology of ITBS as has been historically believed. 1,21,23 However, the increased peak knee internal rotation angle in the ITBS group measured in the current study is likely an important factor in the development of ITBS. A number of authors have suggested that, due to its insertion on the tibia, increased knee rotation increases torsional loads to the tissues of the knee joint such as the iliotibial band.…”
Section: Data Collection and Analysismentioning
confidence: 54%
See 1 more Smart Citation
“…This finding provides further evidence that knee flexion, by itself, does not play a significant role in the aetiology of ITBS as has been historically believed. 1,21,23 However, the increased peak knee internal rotation angle in the ITBS group measured in the current study is likely an important factor in the development of ITBS. A number of authors have suggested that, due to its insertion on the tibia, increased knee rotation increases torsional loads to the tissues of the knee joint such as the iliotibial band.…”
Section: Data Collection and Analysismentioning
confidence: 54%
“…21,26 Anecdotally, this syndrome has been associated with repetitive flexion and extension on a loaded knee, in combination with a tight iliotibial band. 1,16,[21][22][23] Orchard et al 23 suggested that frictional forces between the iliotibial band and the lateral femoral condyle are greatest at 20° to 30° of knee flexion, which occur during the first half of the stance phase of running. However, despite this well-accepted sagittal-plane theory, 1,21,23 no differences have been found in the few biomechanical investi-…”
mentioning
confidence: 99%
“…4,5,10,11 This friction-based understanding was supplemented with the concept of the ITB impingement zone, occurring at around 30 of knee flexion, which was also the most common knee position during foot strike. 11 Fairclough et al 12 refuted this friction model and proposed an etiology based on fascia lata compression through cyclic tension changes within the ITB during gait.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have investigated healthy and IT band injured runners for anatomical and lower extremity running kinematics differences in clinical and research settings (Anderson, 1991;Grady, O'Connor, & Bender, 1986;McNicol, Taunton, & Clement, 1981;Messier & Pittala, 1988;Messier, et al, 1995;Noble C., 1980;Orava, 1978;Orchard, Fricker, Abud, & Mason, 1996;Renne, 1975;Sutker, Barber, Jackson, & Pagliano, 1985). Anatomical factors included knee, forefoot and rearfoot alignments, Q-angle, IT band tightness, and size of the lateral femoral epicondyle.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical factors included knee, forefoot and rearfoot alignments, Q-angle, IT band tightness, and size of the lateral femoral epicondyle. (Anderson, 1991;Grady et al, 1986;McNicol et al, 1981;Messier & Pittala, 1988;Messier et al, 1995;Noble C., 1980;Orava, 1978;Orchard et al, 1996;Renne, 1975;Sutker et al, 1985). Studies involving the leg length discrepancy (LLD) measurement have opposing views of its contribution to IT Band pain: (a) the LLD did not contribute to a person's IT band pain, and (b) 6 of 52 IT band cases experienced pain in the longer leg (Grady et al, 1986;Lindenberg et al, 1984;McNicol et al, 1981).…”
Section: Introductionmentioning
confidence: 99%